2021
DOI: 10.3390/endocrines2020012
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Mobilization in Breast and Prostate Cancer Survivors: The Implications of Altered Stress Hormones Following Acute Exercise

Abstract: Natural killer (NK) cells from the innate immune system are integral to overall immunity and also in managing the tumor burden during cancer. Breast (BCa) and prostate cancer (PCa) are the most common tumors in U.S. adults. Both BCa and PCa are frequently treated with hormone suppression therapies that are associated with numerous adverse effects including direct effects on the immune system. Regular exercise is recommended for cancer survivors to reduce side effects and improve quality of life. Acute exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Interestingly, while some studies showed an inhibitory effect of epinephrine on NK cells 25,26,70 , other in vivo studies demonstrated an increase in NK cell cytotoxicity 31,33,52 . In line with an increased cytotoxicity, our metabolic analysis discovered a prolonged CD16-induced glycolytic activity after β2AR stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, while some studies showed an inhibitory effect of epinephrine on NK cells 25,26,70 , other in vivo studies demonstrated an increase in NK cell cytotoxicity 31,33,52 . In line with an increased cytotoxicity, our metabolic analysis discovered a prolonged CD16-induced glycolytic activity after β2AR stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, epinephrine release during acute stress, exercise or medication can quickly and transiently increase NK cell numbers in peripheral blood [51][52][53] . This may be linked to changes in NK cell adhesion to endothelial cells 54 which is mediated by the integrin LFA-1.…”
Section: β2 Agonists Block Lfa-1 Activity and Cytotoxicity Of Nk Cellsmentioning
confidence: 99%
“…As we previously reported that men with prostate cancer have attenuated epinephrine responses to acute exercise ( 34 ), it interesting that neither T cells (current study) or NK cell mobilization ( 21 ) were adversely impacted. This suggests that other factors may compensate for the reduced epinephrine response, such as changes in shear stress or myokine release ( 41 ).…”
Section: Discussionmentioning
confidence: 99%